Identifikasi Kesalahan Jawaban Mahasiswa pada Mata Kuliah Analisis Real Berdasarkan Newmann’s Error Analysis - Bertu Rianto Takaendengan; Azwar Anwar; Wilson Takaendengan; Putri Ekawati Kobandaha (Universitas Negeri Gorontalo, 2022)
This research aims to identify the student's error in the completion of real analysis using Newman Error Analysis (NEA). The type of research is qualitative descriptive. Which research subjects were 22 students of the mathematics education study program of Universitas Negeri Gorontalo at VI semesters in the 2020/2021 academic year. Data-collection techniques using written tests and interviews. Data is analyzed with reduction, presentation, and drawing conclusion. The result of the study found 4 errors made by students in answering a problem based on NEA: (1) reading, (2) comprehension, (3) transformation, (4) and process skills. This identification can be used by lecturers teaching real analysis to consider supporting the courses and designing learning systems to minimize student errors in solving problems.